Design expert as a statistical tool for optimization of 5-ASA-loaded biopolymer-based nanoparticles using Box Behnken factorial design - Wasim Akram; Navneet Garud (SpringerOpen, 2021)
Abstract Background The overall objective was to prepare a highly accurate nanocarrier system of mesalamine for the treatment of ulcerative colitis with increased therapeutic efficacy and targeting. In the formulation of nanocarrier systems, optimization is a critical process for understanding nanoformulation variables and quality aspects. The goal of the present work was to determine the effect of independent variables, i.e., the concentrations of chitosan, carboxymethyl inulin (CMI), and the drug on the response variables, i.e., particle size and percent entrapment efficiency of the mesalamine-loaded nanoparticle using the Box Behnken design (BBD). The correlation between the independent and dependent variables was investigated using the Design Expert generated mathematical equations, contour, and response surface designs. Result An optimized batch was developed using the ionotropic gel method with selected independent variables (A: + 1 level, B: 0 level, C: − 1 level) and the developed nanoparticles had a particle size of 184.18 nm, zeta potential 26.54 mV, and entrapment efficiency 88.58%. The observed responses were remarkably similar to the predicted values. The morphological studies revealed that the formulated nanoparticles were spherical, and the results of the FTIR and DSC studies indicated the drug-polymer compatibility. The nanoparticle showed less than 5% release in the pH 1.2. In the colonic region (pH 7.4), more than 80 % of the medication was released after 24 h. The kinetics study showed that the Higuchi and Korsemeyer-Peppas models had R 2 values of 0.9426 and 0.9784 respectively, for the developed formulation indicating linearity, as revealed by the plots. This result justified the sustained release behavior of the formulation. Conclusion The mesalamine-loaded chitosan-CMI nanoparticle has been successfully developed using the ionotropic gelation method. The nanoparticles developed in this study were proposed to deliver the drug to its desired site. The developed nanoparticles were likely to have a small particle size with positive zeta potential and high percent drug entrapment. It could be stated from the results that BBD can be an active way for optimizing the formulation and that nanoparticles can be a potential carrier for delivering therapeutics to the colon.